Struktur Kalimat pada Ujaran Penderita Skizofrenia : Studi Kasus di RSJD Dr Amino Gondohutomo Jawa Tengah - Arka Siwi Kinanti; Siti Ulfiyani; Azzah Nayla (Journal on Education, 2025)
This study aims to describe the sentence structure in the utterances of schizophrenics through classification and analysis of sentences uttered by schizophrenics. Both severe schizophrenia, semi-quiet schizophrenia and calm schizophrenia. This research is a type of descriptive qualitative research with data collection techniques simak libat cakap (SLC), recording and note-taking techniques. The research was conducted by listening to conversations between one schizophrenic with fellow sufferers and health workers who handle them. Engage in conversation both actively and receptively with sufferers. In addition, the data analysis used is the Agih method. Data presentation techniques use informal techniques. The results of data analysis of schizophrenia patients have a tendency to utter incomplete sentences which then these incomplete sentences are divided into several types, namely, sequence sentences, exclamation sentences and ellipsis sentences. Schizophrenics also tend to utter incoherent sentences and some other schizophrenics can utter sentences in accordance with Indonesian language rules. The causes of schizophrenia patients experiencing interference when speaking are due to factors (1) thematic structure disorders (2) assembling disorders (3) silence (4) echolalia (5) thought flow disorders